Classic pickup trucks - Mueller, Michael, frey50 (New York : Crestline, 2011)
Mike Mueller tells the complete history of these light trucks in an engaging text filled with facts, legends, and lore. Over 100 color and 100 historical black and white images complement the text.
Includes index.
Keywords: Pickup trucks; Antique and classic cars